ACTIVITY BASED COSTING SYSTEM TERHADAP PENENTUAN BIAYA PRODUKSI PERSPEKTIF EKONOMI ISLAM - Sudarso, aye (Mu'amalatuna: Jurnal Ekonomi Syariah, 2022)
ABSTRACT Cost control will be more ef icient if costs are classified and allocated properly. In the traditional accounting system, production costs are assigned to exclusive and non-exclusive costs. Traditionally, the assignment of costs for non- exclusive costs was carried out on a comprehensive or per departmental basis. This will lead to many cases because the product obtained cannot reflect the actual costs absorbed to make the product. As a result, there will be under-costing and over-costing products. This research is a field research or known as field research. In Islam, production is not just an activity to add value to an object or form new objects to meet needs, but is an output of uniting humans using nature. Humans can seek as much wealth as possible without leaving their obligations to God and others. Justice is the most synchronous value in Islamic Economics. Upholding justice and eradicating injustice is the primary goal of the teachings of His Apostles. Thus, using the Activity Based Costing system, the calculation of production costs is evaluated as better than using the traditional and synchronous system using Islamic economic principles, namely being ready to take risks, not hoarding, not monopolizing, prohibiting interest in usury and social solidarity. Keywords: Activity Based Costing, Production Costs, Islamic Economics ABSTRAK Pengendalian biaya akan lebih efisien jika biaya -biaya diklasifikasikan dan dialokasikan dengan baik. Dalam sistem akuntansi tradisional, pembebanan biaya produksi dilakukan atas biaya eksklusif dan nir eksklusif. Secara tradisional, pembebanan biaya atas biaya nir eksklusif dilakukan memakai dasar pembebanan secara menyeluruh atau per departemen. Hal ini akan mengakibatkan poly kasus lantaran produk yang didapatkan nir bisa mencerminkan biaya yang sebenarnya diserap buat membuat produk. Sebagai akibatnya akan ada produk under costing dan produk over costing. Penelitian ini merupakan penelitian lapangan atau dikenal field research. Dalam Islam produksi bukanlah hanya sekedar aktivitas menambah nilai guna suatu benda atau membentuk benda baru pada memenuhi kebutuhan, namun adalah sebuah output penyatuan insan menggunakan alam. Manusia boleh mencari harta sebanyak-banyaknya tanpa meninggalkan kewajibannya pada Allah dan pula sesama. Keadilan adalah nilai paling sinkron pada Ekonomi Islam. Menegakkan keadilan dan pemberantas kezaliman merupakan tujuan primer ajaran para Rasul-Nya. Dengan demikian, memakai sistem Activity Based Costing perhitungan biaya produksi dievaluasi lebih baik dibandingkan memakai sistem tradisional dan sinkron menggunakan prinsi